Myocysticercosis as a cause of hand swelling: A case report - Ranjit, Niraj; Onta, Pratyenta Raj; Sapkota, Krishna; Wahegaonkar, K; Thapa, Pabin; Thapa, UJ (Nepal Orthopaedic Association Journal, 2020)
Cysticercosis is a common human infestation in developing and underdeveloped countries, that usually presents as neurocysticercosis. It usually involves the brain and eyes, but skeletal muscles and subcutaneous tissues are less commonly affected. We report this case of myocysticercosis as an isolated hand swelling. We want to emphasize that myocysticercosis should be considered as a differential diagnosis in developing countries like ours and surgical excision is needed in most of these cases.